Chad : Second Review Under the Extended Credit Facility Arrangement, and Requests for Waivers of Nonobservance of Performance Criteria and for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Chad's Second Review Under the Extended Credit Facility (ECF) Arrangement, and Requests for Waivers of Nonobservance of Performance Criteria (PCs) and for Modification of PCs. Despite the weaker economy, performance under the ECF-supported program was broadly satisfactory in the first half of 2015, with four of the six PC met, and progress on the structural reform agenda in line with the program objectives. The IMF staff supports the completion of the second review under the ECF arrangement, the waivers of nonobservance for the PCs on contracting of nonconcessional external debt, and nonaccumulation of domestic payment arrears and the modification of PCs.